Teachers and Teaching Assistants – Teamwork as Prevention of School Failure of Pupils During Primary Education [Nauczyciele i asystenci nauczycieli – praca zespołowa jako zapobieganie niepowodzeniom szkolnym uczniów w szkole podstawowej] - Eliášková , Klára; Kučerová , Olga (Studia Edukacyjne, 2023)
This paper investigates the topic of teacher-teaching assistant collaboration in supporting pupils who are at risk of school failure. This topic was addressed, as one of the subtopics, by a longitudinal research study investigating the causes of school failure/success among primary school pupils in the Czech Republic. The aim of the present study is to describe the activities that teaching assistants pursue in relation to “at-risk” pupils or in relation to other pupils in the classroom. The descriptive part of the paper also reviews various forms of teacher-teaching assistant collaboration during the teaching process. This empirical study consists of two parts. In the theoretical introduction, we describe the system of support and advisory services used to implement inclusive education in Czech schools. We also describe the legislative definition of the teaching assistant position and present his/her job description. The empirical part of the paper presents the conclusions of our research survey, which captures how teaching assistance is currently practiced in Czech primary education.